EGG PRODUCTIVITY AND HEMATOLOGICAL INDICATORS OF LAYING HENS UNDER THE INFLUENCE OF PROBIOTIC SUPPLEMENT - Poberezhet, J.; Yaropud, V.; Kupchuk, I. (Scientific Progress & Innovations, 2021)
Numerous feed additives have been used in animal diets in recent years. However, they do not always have a positive effect on product quality. Nowadays, this issue is topical because of advanced technologies introduction for new feeds application, the use of chemical and microbiological synthesis products in animal nutrition. The research objective was to investigate the influence of “Entero-active” probiotic supplement on egg productivity and hematological indicators of laying hens. Probiotics have become widespread among feed additives of natural origin. They create unfavorable pH environment for pathogenic and facultative pathogenic micro-flora, stimulate the growth and biological activity of normal intestinal micro-flora having a positive effect on the composition of the micro-biocenosis, probiotic microorganisms as well as produce biologically active substances and amino acids. The researched “Entero-active” probiotic supplement con-tains lactic acid bacteria of Lactobacillus bulgaricus – 2.0*1010 CCU / kg (colonies of conventional units / kg) and Enterococcus faecium – 2.0*1010 CCU / kg. This feed additive was created at the private enterprise “BTU-Centre” in the town of Ladyzhyn, Vinnytsia region. The experiment lasted for 190 days. The poultry were kept in one-tier group cages following all zoo-hygienic requirements. The control group consumed the basic diet (BD) in the form of complete feed. “Multigain” TM combined feed of “Kyiv-Atlantic-Ukraine” joint-stock company from the village of Myronivka, Kyiv region was used. The researched group was addi-tionally fed with different doses of the probiotics supplement. The control slaughter of poultry was conducted to study hematological parameters at the end of the experiment. It has been established that the consumption of probiotics by the poultry of the 2nd group increased the intensity of laying ability and gross collection of eggs, as compared with the control. In addition, the use of feed additives at feeding the poultry of the 2nd group increased the weight of eggs, small diameter of the dense layer of albumen and yolk in comparison with the control indicator.